Determining if simulation is effective for training in ultrasound: A narrative review. Issue 1 (26th December 2019) - Bradley, Kate; Quinton, Ann; Aziz, Aamer
Abstract: Simulation allows students to learn fundamental skills, such as trial and error, critical thinking, and cognitive and motor skills in a safe environment that closely represents reality. Presently, there are large amounts of literature surrounding simulation in the health and medical field. The aim of this paper is to review the current literature surrounding simulation in medical ultrasound to assess if simulation is effective in teaching sonography skills, and if simulation can be used as a substitute for educating sonography students. A search for literature was conducted through databases such as PubMed, MEDLINE, and CINAHL. Key search terms included ultrasonography [MeSH] and simulation training [MeSH]. Overall, 19 studies were utilised in this review. All the literature concluded that simulation positively affects the learning process of ultrasound trainees. Furthermore, simulation is proven to be a highly valuable tool, which could replace some clinical hours and result in superior student outcomes compared with traditional teaching methods. Simulation however cannot replace traditional teaching methods entirely, and further research is needed to assess how to effectively incorporate simulation into ultrasound education.